2019
DOI: 10.1177/0898264319848579
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Caregiving to Work Conflict and Supervisor Disclosure With Emotional, Physical, and Financial Strain in Employed Family Caregivers

Abstract: Objective: To determine whether employed family caregiver reports of caregiving to work conflict (CWC) are associated with emotional, physical, and financial strain, and whether organizational factors, including supervisor disclosure and caregiver-friendly workplace policies, attenuate these effects. Method: We examined 369 full-time employed caregivers of adults aged 50 years and above from the 2015 AARP and National Alliance for Caregiving population-based study, Caregiving in the United States, using ordina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
7
0
3
Order By: Relevance
“…In Quebec, Tremblay et al (2013) findings amongst Quebec employers showed that the issue was still far from being as well-known as work-family issues related to parenting, with many managers believing that offering some degree of flexibility is enough to satisfy carer employees' needs. Recent findings indicate a lack of formal human resources (HR) policies specific to adult and elder care within workplaces, leading to a reliance on benevolent supervisory discretion (Murphy and Cross, 2018), while there is evidence that disclosing one's caring responsibilities to a supervisor increases emotional, physical and financial strain for employed carers (Templeman et al, 2019) and might contribute to stigma around the use of CFWPs (Ramesh et al, 2017). There is thus an apparent need for formal adult and elder care policies in workplaces which protect employed carers.…”
Section: Availability Of Cfwps Around the World And In Quebec Organiz...mentioning
confidence: 99%
See 4 more Smart Citations
“…In Quebec, Tremblay et al (2013) findings amongst Quebec employers showed that the issue was still far from being as well-known as work-family issues related to parenting, with many managers believing that offering some degree of flexibility is enough to satisfy carer employees' needs. Recent findings indicate a lack of formal human resources (HR) policies specific to adult and elder care within workplaces, leading to a reliance on benevolent supervisory discretion (Murphy and Cross, 2018), while there is evidence that disclosing one's caring responsibilities to a supervisor increases emotional, physical and financial strain for employed carers (Templeman et al, 2019) and might contribute to stigma around the use of CFWPs (Ramesh et al, 2017). There is thus an apparent need for formal adult and elder care policies in workplaces which protect employed carers.…”
Section: Availability Of Cfwps Around the World And In Quebec Organiz...mentioning
confidence: 99%
“…This may mean that small employers are more willing to find solutions on an informal basis for employed carers. The problem is that informality entails certain downsides, such as stigma, reliance on supervisory discretion and invisibility of care in the workplace (Murphy and Cross, 2018;Templeman et al, 2019), which is why formal measures are important for carers (Concilivi, 2021). There may be greater access to elder care resources through an EAP in large organizations.…”
Section: Ijssp 435/6mentioning
confidence: 99%
See 3 more Smart Citations